Concept paper on the technique of cryopreservation, removal and transplantation of ovarian tissue for fertility preservation = Konzeptpapier zur Technik der Kryokonservierung, Entnahme und der Transplantation von Ovarialgewebe zum Fertilitätserhalt - Beckmann, Matthias Wilhelm; Germeyer, Ariane; Sütterlin, Marc (Geburtshilfe und Frauenheilkunde, 2019)
The cryopreservation of ovarian tissue with subsequent transplantation of the tissue represents an established method of fertility protection for female patients who have to undergo gonadotoxic therapy. The procedure can be performed at any point in the cycle and thus generally does not lead to any delay in oncological therapy. With the aid of this procedure, more than 130 births to date worldwide have been able to be recorded. The birth rate is currently approximately 30% and it can be assumed that this will increase through the further optimisation of the cryopreservation and surgical technique. The concept paper presented here is intended to provide guidance for managing cryopreservation and transplantation of ovarian tissue to German-speaking reproductive medicine centres.
Publikationsdatum: 09. October 2018 (eFirst)
Gesehen am 12.07.2019